Assessment of Antioxidant and Antimicrobial Property of Polyphenol-Rich Chitosan-Pineapple Peel Film - Jyoti Jatav; Ayon Tarafdar; Chakkaravarthi Saravanan; Bhaswati Bhattacharya (Journal of Food Quality)
This work aimed to evaluate the antioxidant and antimicrobial capacities of pineapple peel extract-incorporated chitosan films to establish its utility as an active food packaging film. Total phenol and total flavonoids in ethanolic pineapple peel extract (11.1 ± 0.82 mg GAE/g sample, 3.86 ± 0.4 mg Quercetin/g sample) were determined to be higher than those in methanolic pineapple peel extract (7.98 ± 0.55 mg GAE/g sample, 2.37 ± 0.13 mg quercetin/g sample) and higher antioxidant activity was observed for pineapple peel ethanolic extract (PEE). Similarly, PEE-enriched chitosan film also reported greater antioxidant activity compared to pineapple peel methanolic extract (PME)-incorporated chitosan film. The total phenols, flavonoids, and significant antioxidant activity were accounted due to the contents of ferulic acids, quercetin, and kaempferol in both PEE and PME quantified via triple quadrupole LC/MS/MS system. These alcoholic extracts exhibited significant inhibitory zones against both Gram-positive (Bacillus cereus, Staphylococcus aureus) and Gram-negative (Escherichia coli, Salmonella typhimurium) food-borne bacterial strains. PME exhibited the lowest minimum inhibitory concentration and minimum bactericidal concentration (0.625 mg/ml) against B. cereus. Pure chitosan films at ≥7 log CFU/ml after 24 h showed lower log reduction for all the bacterial organisms, whereas the chitosan-PEE (at ≤5 logs CFU/ml) and chitosan-PME (at ≤6 log CFU/ml) films expressed higher log reduction for all the four bacterial isolates. Thus, this work led to the utilization of the pineapple peel waste as well as provided an alternative to nonbiodegradable packaging films.